Organisational and economic characteristics of agriculture in Poland from areas especially predisposed for the delivery of public goods - Zieliński, Marek (Cechy organizacyjne i ekonomiczne rolnictwa w Polsce z obszarów szczególnie predestynowanych do dostarczania dóbr publicznych, 2022)
The aim of the study is to assess the organisational and economic characteristics of agriculture in Poland from areas (communes) especially predisposed to provide public goods. The delimitation of these communes was carried out on the basis of the agricultural production area valorization index (APAV) established by the Institute of Soil Science and Plant Cultivation – State Research Institute (IUNG – PIB) in Pulawy. Production potential of agriculture in these communes were obtained from the Agency for Restructuring and Modernization of Agriculture (ARMA). In addition, data from the Statistics Poland (GUS) and Polish FADN were used. It was stated that farms from these communes in comparison to farms from other communes were characterised by, among others, lower total costs per 1 ha of UAA, lower productivity of factors of production and income per 1 ha of UAA. The operating subsidies received were of great importance to them, without which they would often suffer losses.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 3, s. 165-181
Keywords: agriculture from ANCs areas; organic farming; afforestation; organizational and economic potential of agriculture; public goods; common agricultural policy; rolnictwo z obszarów z ograniczeniami naturalnymi lub innymi szczególnymi ograniczeniami; rolnictwo ekologiczne; zalesienie; potencjał organizacyjny i ekonomiczny rolnictwa; dobra publiczne; wspólna polityka rolna